A inclusão dos LGBTs no serviço público: um estudo nas secretarias estaduais do Tocantins - Cruz, Jessika Villalon Sousa (Universidade Federal do Tocantins, 2021)
This research talks about the insertion of LGBT workers in the public service, within the scope of the Municipality of Palmas and the state public service. At first, it discusses the need to implement public policies aimed at the LGBT population. The theoretical basis was based on the studies of Butler (2003), Foucault (2010), Irigaray (2008) and Melo, Avelar and Maroja (2012). Next, an analysis was made from the creation of public policies in the world, as well as an overview of the actions that take place in some parts of the world. Soon after, it gives an overview of public policies and the insertion of LGBT civil servants in public organizations. Questionnaires were applied to civil servants who worked in public organizations, in the state of Tocantins, as well as in the Municipality of Palmas. The questionnaires contained 30 semi open questions, which were answered on the condition of anonymity. Thus, the sample of ten servers was defined as a non-random sample, according to Barbetta (2012). After data collection, the interviews were transcribed and the data analyzed. For the analysis of the data generated, the assumptions of the content analysis according to Bardin (2011) were used. The results showed that all LGBT servers reinforce their speeches about the implementation of actions and improvements, with regard to their inclusion and acceptance in the organizations where they work. It was evidenced that the LGBT public servants of the State of Tocantins do not feel included in their organizations and do not perceive public policies coming from the State Government, being the only existing policies those of a federal nature. Finally, the reports of the employees about their experiences in their work environments were presented, and improvements in management were suggested by the Municipality of Palmas, as well as the Government of the State of Tocantins.